2003
DOI: 10.1099/vir.0.18633-0
|View full text |Cite
|
Sign up to set email alerts
|

Ets-2 Repressor Factor (ERF) mediates repression of the human cytomegalovirus major immediate-early promoter in undifferentiated non-permissive cells

Abstract: The repression of human cytomegalovirus immediate-early (IE) lytic gene expression is crucial for the maintenance of the latent viral state. By using conditionally permissive cell lines, which provide a good model for the differentiation state-dependent repression of IE gene expression, we have identified several cellular factors that bind to the major immediate-early promoter (MIEP) and whose expression is down-regulated after differentiation to a permissive phenotype. Here we show that the cellular protein E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 43 publications
6
59
0
Order By: Relevance
“…Combined with the results discussed above that PU.1 and Spi-C have opposing activities on the Fc␥RIIb and IgH genes, our data suggest that Spi-C can inhibit PU.1 DNA binding either directly or indirectly. This type of inhibition is also observed with Ets-2 repressor factor, which acts as a repressor to Ets-2 activity (64). Therefore, we propose that when Spi-C expression is induced during normal B cell development, it inhibits PU.1 binding to target genes.…”
Section: Discussionmentioning
confidence: 73%
“…Combined with the results discussed above that PU.1 and Spi-C have opposing activities on the Fc␥RIIb and IgH genes, our data suggest that Spi-C can inhibit PU.1 DNA binding either directly or indirectly. This type of inhibition is also observed with Ets-2 repressor factor, which acts as a repressor to Ets-2 activity (64). Therefore, we propose that when Spi-C expression is induced during normal B cell development, it inhibits PU.1 binding to target genes.…”
Section: Discussionmentioning
confidence: 73%
“…While ERF was previously shown to bind to and repress the human cytomegalovirus major immediate-early promoter, 31,32 endogenous cellular target genes have not been defined. The present studies demonstrating the ability of ERF to repress c-myc, and cdc2, previously identified as transcriptional targets of METS, is consistent with the high degree of sequence conservation of the ETS domains of METS and ERF that mediate sequence-specific DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…When growth factors are removed, ERF is dephosphorylated and transported back to the nucleus. 27,28,30 While inactivation of ERF by Ras/MAPK signaling has been demonstrated to be involved in erythroid differentiation and ERF has been shown to bind to and repress the human cytomegalovirus major immediate-early promoter (MIEP) in undifferentiated cells, 31,32 endogenous cellular targets of ERF and the molecular mechanisms responsible for its repressor function have not have been defined.…”
Section: Introductionmentioning
confidence: 99%
“…In direct contrast was the association of the MIEP with markers of transcriptional repression (Fig. 3b, lane 4) - probably due to the continued action of transcriptional repressors YY1 and ERF and the chromatin-remodelling enzymes with which they interact (Bain et al, 2003;Liu et al, 1994;Murphy et al, 2002;Wright et al, 2005).…”
mentioning
confidence: 88%